PENGARUH LINGKUNGAN KERJA DAN JENJANG KARIR TERHADAP KEPUASAN KERJA KARYAWAN DI PT. SUWARNA DWIPA MAJU TANGERANG - Teguh Dikdaya; Muhammad Richo Rianto (Jurnal Bina Bangsa Ekonomika, 2023)
PT. Suwara Dwipa Maju, is a service company that focuses on Information Technology and Telecommunication Systems and Lighting Specialists needed by both government agencies, private companies, hotels, apartments and residents. This observation aims to determine the impact of the Work Environment and Career Path on employee retention at PT. Suwarna Dwipa Maju Tangerang. The results of this observation show that the work environment has a positive influence on employee work. The fairly good environment is said to be good and this affects employee job satisfaction in the company. The good environment is due to the comfort and safety of employees while working. As well as employee career development at PT. Suwarna Dwipa Maju Tangerang is still in the good enough category so that career influences employee job satisfaction